2015
DOI: 10.1111/jocn.12792
|View full text |Cite
|
Sign up to set email alerts
|

Predictors ofHIVenacted stigma among Chilean women

Abstract: Aims and objectives To investigate if socio-demographic factors, religiosity, HIV-related knowledge, Marianismo, history of having been tested for HIV, knowing someone who died of AIDS and HIV risk perception were predictive factors to HIV enacted stigma predictors among Chilean women. Background HIV infection is the number one cause of death among women during their reproductive years. In Chile, studies with people living with HIV demonstrate the existence of HIV-related stigma. However, limited evidence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…This has been underlined in Ho and Mark's concept [73] asserting that societies that emphasise collectivism, such as in Indonesia, can blame or stigmatise the entire extended family if one among family members is infected with HIV. This seemed to be one of the cultural factors that contributed to anticipated stigma among the study participants, leading to participants concealing their HIV status [74][75][76]. Concealment of HIV status from other community members may also lead to the lack of social support for PLHIV, which has been reported to lead to HIV stigma and discrimination against PLHIV [77,78] and poor access to HIV healthcare services [79], a vicious cycle.…”
Section: Discussionmentioning
confidence: 98%
“…This has been underlined in Ho and Mark's concept [73] asserting that societies that emphasise collectivism, such as in Indonesia, can blame or stigmatise the entire extended family if one among family members is infected with HIV. This seemed to be one of the cultural factors that contributed to anticipated stigma among the study participants, leading to participants concealing their HIV status [74][75][76]. Concealment of HIV status from other community members may also lead to the lack of social support for PLHIV, which has been reported to lead to HIV stigma and discrimination against PLHIV [77,78] and poor access to HIV healthcare services [79], a vicious cycle.…”
Section: Discussionmentioning
confidence: 98%
“…Lower levels of education may lead to less exposure, lack of or little knowledge about HIV infection and transmission. In contrast, higher levels of education might lead to higher levels of knowledge, providing exposure to new ways of thinking and new sources of information about the HIV pandemic resulting in the reduction of less supportive attitudes towards PLWHA 79 80. Previous research has demonstrated that people with high levels of knowledge of the transmission routes for HIV consistently had more supportive attitudes towards those with HIV demonstrating the role that knowledge has in reducing the misconceptions that act to create fear and shape stigma 79…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of education in this sample might have affected findings on internalized stigma, as previous research has shown protective effects of higher education levels with regards to stigma, mental health, and HIV risk. 31,32 Therefore, the low levels of internalized stigma found in our sample may not be representative of stigma among MSM in western Kenya. Different recruitment approaches may be needed to confirm and extend the results presented here.…”
Section: Discussionmentioning
confidence: 84%